Estimating Model Life Tables using both Abridged Life Table and Brass Relational Two- parameter Logit System in Twenty Six States in Sudan From the Population Census Data (2008) - Awad, Sulima Mohamed (Gezira Journal of Economic and Social Sciences; مجلد 7 عدد 2 (2016), 2016)
The objective of the study is to enhance methodology in the area of adult mortality and to attempt to correct defective data in Sudan and the twenty-six Stats to estimate adult mortality and life table using Brass relational two-parameter logit system, also to estimate the probability of dying and expectation of life at birth using adjusted data in the twenty-six States in Sudan through Brass relational two-parameter logit system. A comparison was made between the adjusted life table for Sudan and the twenty-six Stats with the original Abridge model life table in order to test the reliability of the method used. The data was gathered from Population Census Data 2008. Values for e 0 calculated by Brass Logit System when compared with those calculated using the abridge life table, were reasonable and realistic, the abridge life table e 0 might be affected by the defective data .Life expectancy e 0  for the whole country found to be 59 years using abridge life table, where Life expectancy calculated using Brass method found to be 54 years, in Gezira, Eastern Equatoria, Nahr El Nile, Northern and Sinnar states Life expectancy e 0  equal to 74,72 71, 75and 72 years respectively, where e 0 values calculated by Brass Logit System for the same group of states were 58, 56, 58, 59 and 57 respectively. In Northern Bahr El Ghazal, Unity and Warrap, Bahr El Ghazal e 0 values rise from 30, 30, 44, and 46 to 44, 55, 54 and 51respectively after using Brass Logit System. In Sudan    , indicates low mortality relative to the standard, Blue Nile, Northern Bahr El Ghazal, West Darfur have positive values of  indicates high mortality relative to the standard. North Kordfan state  = -2.545524 out of the reasonable range. In Sudan and Blue Nile high value of  indicates a low infant and child mortality and a high adult mortality relative to the standard. The majority of states recorded a value of higher than the upper limit of the reasonable range , except Al Gadarief reported indicates a high infant and child mortality and low adult mortality.